TATA KELOLA DANA DESA DALAM PEMBANGUNAN DI DESA BELOBATANG KECAMATAN NUBATUKAN KABUPATEN LEMBATA TAHUN 2021 - Darius Buja Wutun; Mikael Thomas Susu; Frans Bapa Tokan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
The Village Fund provides a very strategic position for the village. With the existence of a very large Village Fund, the village government is required to manage village finances wisely. In accordance with Law No. 6 of 2014 concerning Villages which explains that village financial management must comply with the principles of accountability, transparency, participation and be carried out in an orderly and budgetary manner. This research explains the management of Village Funds in development in Belobatang Village, Nubatukan District, Lembata Regency. The Belobatang Village Government must be accountable in managing Village Funds, so that the benefits can be felt by the community. This study used descriptive qualitative method. The data collection technique in this research is in-depth interview techniques and documentation. From the concluded results, recommendations or suggestions can be made for the Belobatang village government to follow the procedures and schedule that have been set so that the development work carried out can reach the target.